How Do Servant Leadership and Knowledge Sharing Trigger Innovative Work Behaviors among Millennials at Start-up Businesses? - Putri Rahma Dayanti; Praptini Yulianti (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Purpose:Technological developments and environmental changes are currently growing rapidly. This adaptation indirectly requires a company to continue to innovate, especially in the development of Start Up software. This study aims to examine the relationship between servant leadership and knowledge sharing on innovative work behavior. This study also explores the mediating role of creative self-efficacy on innovative work behavior. Design/methodology/approach: Data was collected from 120 millennial Start Up employees in the field of software development. Data collection was carried out through a survey design. Data analysis was done through a structural equation model using PLS-Smart. Findings: The results show that servant leadership and knowledge sharing have a significant positive effect on innovative work behavior. Creative self-efficacy partially mediates the relationship between servant leadership and innovative work behavior. Creative self-efficacy is also able to partially mediate the relationship between knowledge sharing and innovative work behavior. Originality/value: This study contributes to the existing literature by integrating the mechanism between servant leadership and knowledge sharing into innovative work behavior. Practical implications: This study provides prospective insights to management leaders and practitioners that servant leadership and knowledge sharing bring about positive change in the innovative work behavior. It also augments innovative behavior by enhancing employees' creative self-efficacy, especially millennials in Start-Up businesses.